THUR 196 Pregnancy outcomes in alemtuzumab-treated rrms patients. Issue 10 (13th September 2018) - David, Rog; Jiwon, Oh; Christina, Chambers; Kerstin, Hellwig; Pamela, McCombe; Luke, Chung; Nadia, Daizadeh; S, Compston D Alastair
Abstract : Murine studies show no alemtuzumab-related teratogenicity, but no controlled human clinical studies of alemtuzumab in pregnancy exist. In phase 2 (CAMMS223 [NCT00050778 ]) and phase 3 (CARE-MS I [NCT00530348 ], CARE-MS II [NCT00548405 ]) studies, patients received 2 annual alemtuzumab courses. Two extension studies provided longer-term evaluation (NCT00930553 ; TOPAZ [NCT02255656 ]). Pregnant/lactating patients were ineligible for further treatment but were followed up for safety. As of 1 April 2017, 248 pregnancies occurred in 156/972 alemtuzumab-treated female patients (mean [SD] age at conception, 32.5 [4.4] years; mean [SD] time from last alemtuzumab dose to conception, 33.5 [22.6] months; 16 within 4 months of dosing), with 218 completed, 14 ongoing, and 16 with unknown outcomes. Of completed pregnancies with known outcomes, 147 (67%) were live births with no congenital abnormalities or birth defects. There were 48 (22%) spontaneous abortions, 22 (10%) elective abortions, and 1 (0.5%) stillbirth. To date, there has been no signal for teratogenicity. Incidence of spontaneous abortions was comparable with treatment-naive MS patients (5%–21%) and the general population (17%–22%). Real-world data are currently collected by the International Lemtrada Pregnancy Exposure Registry, a prospective, non-interventional, observational safety study enrolling patients in ≥19 countries who become pregnant within 4 months of alemtuzumab exposure. Study Support: Sanofi.